ARABIC AMIYAH FOR PILGRIMS (Study 8 KBIH in District / City of Pekalongan 2015) - Moch Lukluil Maknun (Al-Qalam, 2016)
Every pilgrims hope to getting Hajj Mabrur. One effort to commercialize the Hajj Mabrur is able to run all the pilgrimage circuit and perfect in it, while also maintaining a good relationship with others, or in terms of the law called hablun minallah and hablun minannas. One effort to be able to maintain good relations with others is to understand and interact with a language that can be understood by both sides, in this case is Arabic language. With naturalisik methods, and qualitative analysis, the core of this paper would like to state that the Arabic Amiyah still used and continues to grow until now; learning Arabic Amiyah for pilgrims can be regarded as complementary needs; there are various constraints experienced in learning Arabic Amiyah by KBIH for pilgrims; and the state of Arabic language books for pilgrims are still rare and that there is still very simple.